Tratamento da Apneia Obstrutiva Grave do Sono por meio de Aparelhos Intraorais Modificados - Jorge Machado Caram (2021)
Obstructive Sleep Apnea Syndrome (OSAS) is a respiratory disease of high prevalence, mortality, and morbidity, considered as a risk factor for cardiac, metabolic, neurological and perioperative morbidities, being characterized by recurrent upper airway obstructions during sleep. Clinically, the disease manifests itself through respiratory pauses, non-restorative sleep, fatigue and and/or insomnia, abrupt awakening with choking and, often, snoring. It severely affects patients’ quality of life, work capacity and causes excessive daytime sleepiness that, associated with automobile and industrial accidents, justifies seeking for solutions. Effective treatment of the disease is still a matter of controversy. Positive Airway Pressure Ventilation devices (PAP), although the gold standard treatment, encounter their limitation in patients' resistance to the discomfort and social obstacle represented by the equipment. Oral Appliances (OA) emerge as an option, as they compensate for lower efficacy with greater comfort and accessibility, presenting satisfactory performance when indicated for milder cases. Among OA, literature better entitles those which act indirectly on the tongue and tissues of the pharynx through mandibular advancement – known as Mandibular Advancement Device (MAD). PAP intolerance, associated with the limited effectiveness of MAD, contributes to the emergence of a gap, especially when it comes to more severely affected patients. This thesis, with a retrospective approach, intended to evaluate a modified MAD, aimed mainly at these severe patients, by means of two articles generated by this work and related to each other. The objective was to verify if this modification would provide greater efficiency than the use of the previously MAD. The first article “The effectiveness of modified intraoral mandibular advanced appliances aimed to treat severe sleep obstructive apnea”. Two MADs are compared across 194 critically ill patients divided into two groups. One of the groups used the MAD consecrated by the literature, while the other group used a modified MAD, to simultaneously provide a direct and stabilizing intervention on the tongue. The results confirmed the pertinence of the hypothesis. The second article, entitled “Mandibular advancement device associated with tongue control: a new option for the treatment of obstructive sleep apnea?”, sought to investigate the influence of the tongue on the failures obtained with MADs. In this article, twenty patients that had been previously submitted to MADs that had ineffectiveness as an outcome were evaluated. The same twenty patients were subsequently treated with the modified MAD to provide direct intervention on the tongue. The aim was to verify if this procedure could reduce the previous failure rate. With the modified MAD the number of responding patients rose from 20% to 75%, suggesting that the tongue plays an active substantial role in cases where MADs were previously ineffective. The relation between these articles was designed, by means of contrasting distinct approaches that complement one another on the influence of the tongue on the performance of MADs.